PLAN DE NEGOCIOS PARA PRODUCTOS TURÍSTICOS EN LA FINCA CAFETALERA “LEÓN TOLEDO” PERTENECIENTE A LA PARROQUIA DE SAN PEDRO DE VILCABAMBA, CANTÓN LOJA - Neira Calderón, Claudia del Cisne (2017)
Tourism has become one of the main axes of international trade, and represents at the same time one of the largest sources of income for many developing countries. In Ecuador there are several business plan initiatives focused on tourism, with the purpose of increasing the number of travelers, increasing the supply of services, promoting destinations, as well as enhancing sustainable development and improving the quality of life of the habitants. To the south of the Loja it´s located San Pedro de Vilcabamba, which has a great natural and cultural wealth. Here you can find the "Leon Toledo" coffee farm, which has a strategic location, favorable climate and unparalleled vegetation. Has not been inserted in the tourist activity for which it was proposed to carry out a Business Plan for tourism products in the coffee farm "Leon Toledo" To carry out the present research project entitled: Business Plan for tourism products in the coffee farm "Leon Toledo" belonging to the San Pedro de Vilcabamba, was established as general objective: Elaborate a Business Plan for products in the "León Toledo" coffee farm, three specific objectives were derived: the first one was to carry out a tourist diagnosis of the current situation of the "Leon Toledo" coffee plantation; For which the deductive method was applied the same one that was focused to know the situation in which is the property; As well as the inductive method which allowed us to approach real data of the parish and its attractions, the analytical method that served to carry out an in-depth analysis of the reality of each of the tourist attractions of the parish, as well as techniques such as observation Direct, survey, interview, as well as MINTUR tourist attraction inventory and summary to describe and evaluate the natural and cultural tourist attractions in the study site and in its surroundings, finally the FODA Matrix was used and matrix of strategies. The second objective was to propose the business plan for tourism products in the coffee farm "Leon Toledo"; In the same one was used the analytical method that determined the processing of the information that is structured in several studies like the market studies where the supply and the demand of the future company of tourist services was analyzed. Technical Study where the size and location of the project was determined, Administrative Study which the organizational structure was established as the company is legally constituted, Financial Study analyzed the investment necessary to start the business with an amount of $36,517,56 , whose financial assessment indicates a VAN of $ 30,617,36, a TIR of 41%, a RB / C of 0.70 cents, recovering the investment in 2 years, 7 months and 21 days, in a Sensitivity of 36,35% in increasing costs and a 24,27%. in the decline in income. The third objective was the socialization of the proposal of the business plan for tourist products to the authorities and community.